Analisis Keselamatan dan Kesehatan Kerja (K3) Dengan Metode Fault Tree Analysis (FTA) Pada PT. Surya Karya Setiabudi - Sefiani Adella, Tyas; Yuamita, Ferida (Jurnal Etnik: Ekonomi-Teknik, 2023)
The problems that exist at PT. Surya Karya Setiabudi is employee negligence which can result in work accidents. The number of workplace mishaps that occurred at the company in 2021 was 26 cases.The goal of this research is to identify the value of K3 statistics and find out the sources of work failures that exist in the company. The Fault Tree Analysis (FTA) approach was utilized in this investigation to determine what elements cause work failure.The results of calculating the statistical value of K3 Frequency Rate obtained 553.3/1 million operating hours, Severity Rate 1,404/1 million operating hours, and the safe T-score is 0. The FTA analysis results suggest that there is a lack of safety induction is the main cause of the human factor that can cause accidents such as not being careful when working such as being in a hurry when doing work, when welding the distance between the face and the object is less than 50 cm, not using PPE such as employees forgetting to wear welding goggles, forgetting to wear gloves, lack of awareness of employees work safety and lack of awareness of employees about the importance of PPE, not being serious at work such as being too tired so employees feel bored or bringing external problems while working so they don't focus. Another factor that causes employees not to use PPE is the lack of PPE monitoring from K3 staff.Factors causing accidents in companies are mostly caused by humans. From the FTA analysis, it can be seen that the lack of safety induction is the main cause of the human factor.